Unravelling challenges of higher education institutions in implementing effective micro-credentials: a multi-stakeholder qualitative study / Fauziah Saadah Abdul Halim, Johan Eddy Luaran and Lee Sze Seau Jill - Abdul Halim, Fauziah Saadah; Luaran, Johan Eddy; Lee, Sze Seau Jill (Universiti Teknologi MARA, 2024)
In response to the evolving educational landscape where employers are searching for individuals with specific skills aligned with the swiftly changing market needs, universities worldwide, including those in Malaysia, are increasingly interested in micro-credentials. Identifying challenges in micro-credential adoption is crucial for various stakeholders, including course developers, policy makers, government agencies, and industry bodies. This research aims to examine the challenges faced by multi-stakeholders in higher education institutions while adopting micro-credential as viable alternatives and formal credentialing systems. This qualitative study employed semi-structured individual interviews involving 20 higher education stakeholders. The interviews were audio-recorded, transcribed, and analysed using structured qualitative content analysis in MAXQDA, with Lincoln and Guba’s criteria guiding the analysis process to ensure rigour. The study identified five factors that challenge the adoption of micro-credentials: learners, developers, organisational, industries, technological factors. Based on these factors, recommendations for addressing these challenges were proposed. It is hoped that a more informed and nuanced understanding of these challenges will enable Malaysian educational institutions and policymakers to devise effective strategies to overcome barriers and create a robust micro-credential ecosystem that addresses the needs of learners and future employers.